2022
DOI: 10.1186/s12862-022-01999-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variation in baboons from central Mozambique unveils complex evolutionary relationships with other Papio species

Abstract: Background Gorongosa National Park in Mozambique hosts a large population of baboons, numbering over 200 troops. Gorongosa baboons have been tentatively identified as part of Papio ursinus on the basis of previous limited morphological analysis and a handful of mitochondrial DNA sequences. However, a recent morphological and morphometric analysis of Gorongosa baboons pinpointed the occurrence of several traits intermediate between P. ursinus and P. cynocephalus, leaving open the possibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Importantly, baboons of Gorongosa National Park experience a mosaic of habitats including closed-canopy savannah, rainforest, montane grasslands, rivers, and caves [ 42 , 43 , 44 , 45 ]. Modern environments analogous to the ones inhabited in the past by Australopithecines 4.2 to 2.3 million years ago “certainly included present day Gorongosa National Park” [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, baboons of Gorongosa National Park experience a mosaic of habitats including closed-canopy savannah, rainforest, montane grasslands, rivers, and caves [ 42 , 43 , 44 , 45 ]. Modern environments analogous to the ones inhabited in the past by Australopithecines 4.2 to 2.3 million years ago “certainly included present day Gorongosa National Park” [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Today, numerous projects are underway in GNP. These studies use a combination of methods including motion-triggered cameras (Gaynor et al, 2018(Gaynor et al, , 2021Easter et al, 2019), biologgers (often including Global Positioning System units, triaxial accelerometers, and sometimes video recorders; e.g., Branco et al, 2019a,b;Becker et al, 2021;Bouley et al, 2021), aerial counts (Cumming et al, 1994;Dutton and Carvalho, 2002;Dunham, 2004;Stalmans, 2012;Stalmans et al, 2019), animal follows (Hammond et al, 2022), molecular studies (Martinez et al, 2019;Santander et al, 2022), and other field observation tools (e.g., Muschinski et al, 2019) to gain insights in the park's ecology. The δ 13 C enamel , δ 15 N enamel , and δ 18 O enamel datasets of Gorongosa's fauna presented here-the first stable isotopes result for any terrestrial fauna in Mozambique-will help us to better understand dietary patterns of the large-bodied animals which roam GNP today.…”
Section: Greater Kudumentioning
confidence: 99%
“…The δ 15 N enamel values for omnivores are significantly different from those of carnivores, but not herbivores (Figure 3A and Table 1). Our omnivore dataset includes seven baboons (Papio ursinus with genetic variants of P. cynocephalus, Santander et al, 2022) and two bushpigs (Potamochoerus larvatus); the two taxa are indistinguishable in their δ 15 N enamel values.…”
Section: Omnivore δ 15 N Enamelmentioning
confidence: 99%
“…Based mainly on samples from captive individuals without clear geographic provenance, Boissinot et al [ 42 ] identified chacma baboons as diverging first and yellow baboons second, and a northern clade with hamadryas, olive, and Guinea baboons, in which Guinea baboons diverge first. Y-chromosomal data also support the “north-south split” hypothesis, with Kinda baboons diverging first in the southern clade and hamadryas baboons diverging first in the northern clade [ 43 ]. Phylogenetic reconstructions based on Alu insertion polymorphisms found intergeneric introgression between Papio and Theropithecus , a southern clade in which chacma and Kinda baboons are most closely related to the exclusion of yellow baboons, and a northern clade in which Guinea and olive baboons are most closely related to the exclusion of hamadryas baboons [ 44 , 45 ].…”
Section: Disentangling the Phylogeny Of Baboonsmentioning
confidence: 82%
“…Importantly, chacma and yellow baboons are characterized by mitochondrial paraphyly, which can probably be attributed to introgressive hybridization and nuclear swamping due to the invasion of chacma baboon males into originally yellow baboon populations further north [ 33 , 49 ] ( Figure 3 ). Detailed investigations of phenotypic characters in the putative current contact zone of southern yellow and northern chacma baboons in Gorongosa National Park are suggested as evidence for past and/or ongoing hybridization between these populations [ 53 ], but genomic data have not found any support for recent gene flow [ 43 ]. Possibly, Luangwa Valley baboons represent hybrids between yellow, Kinda, and chacma baboons, but there is no genetic evidence available yet.…”
Section: The Cradle Of Baboons: Introgressive Hybridization Between S...mentioning
confidence: 99%